2004
DOI: 10.1051/forest:2004065
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization at planting impairs root system development and drought avoidance of Douglas-fir (Pseudotsuga menziesii) seedlings

Abstract: -Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) seedlings (1 + 1 bareroot) were divided into 8-13 cm 3 and 23-35 cm 3 initial root-volume categories and either not fertilized or fertilized with 60 g Apex ® in the planting hole at a drought-prone clearcut site in the Oregon Coast Range, USA. Regardless of initial root volume, fertilized seedlings consistently reached lower predawn xylem water potential (Ψ xylem ) values than non-fertilized seedlings during summer. Roots did not proliferate relative to ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 46 publications
2
33
0
1
Order By: Relevance
“…This suggests that large initial root system size does not confer drought avoidance in bareroot northern red oak seedlings, as was similarly reported for Douglas-fir seedlings (Haase and Rose, 1993;Jacobs et al, 2004a), and that large planting stock should be targeted for sites with relatively higher soil moisture availability. Transplant shock in northern red oak seedlings was implicated by reduced Ψ L , A, E, and growth.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This suggests that large initial root system size does not confer drought avoidance in bareroot northern red oak seedlings, as was similarly reported for Douglas-fir seedlings (Haase and Rose, 1993;Jacobs et al, 2004a), and that large planting stock should be targeted for sites with relatively higher soil moisture availability. Transplant shock in northern red oak seedlings was implicated by reduced Ψ L , A, E, and growth.…”
Section: Discussionsupporting
confidence: 48%
“…No differences were found in Ψ L at 95 or 115 d in Douglas-fir seedlings graded into different Rv classes and transplanted into pots (Haase and Rose, 1993). Similarly, Jacobs et al (2004a) reported no significant differences in Ψ L between RvC for Douglas-fir seedlings following field transplant. Contrary to above results, we observed that northern red oak seedlings with larger initial Rv were less able to mitigate effects of drought following transplant, as indicated by lower Ψ L values (Fig.…”
Section: Root Volume Alters Seedling Physiology and Growth Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this positive response was not maintained after outplanting and contrasted with other recent studies conducted in Mediterranean conditions that suggested that a high nutrient supply generates early root growth and a positive carbon balance that helps sustain the demand for resources to maintain growth biomass , Cuesta et al 2010, VillarSalvador et al 2012. The low RDM could be attributed to the effects of residual nutrients from the fertilizer contained within the polymer-coated fertilizer, and the root plug, which tends to inhibit the growth ability of roots in the planting hole under low soil water available (Idris et al 2004, Jacobs et al 2004. By contrast, in more temperate and wet environments, CRF promoted root development (Timmer & Teng 2004, Haase et al 2006.…”
Section: Morphological Responses Of Seedlingsmentioning
confidence: 99%
“…By contrast, high seedling N loading in the nursery produced a morphological imbalance by increasing shoot biomass over root biomass following planting (Trubat et al 2008, Cortina et al 2013. Under dry conditions, this morphological imbalance increases transpiration rates and reduces stem water potential, root hydraulic conductivity (Hernández et al 2009), and stomatal conductance (Jacobs et al 2004). Low shoot:root ratios could promote a more conservative water use and improve the likelihood of survival after outplanting (Leiva & Fernández-Alés 1998, Lloret et al 1999.…”
Section: Introductionmentioning
confidence: 99%